Placental site nodule: A tumor-like trophoblastic lesion - Jacob Sunitha; Mohapatra Debahuti (Wolters Kluwer Medknow Publications, 2009)
Placental site nodule is an uncommon, benign, generally asymptomatic lesion of trophoblastic origin, which may often be detected several months to years after the pregnancy from which it resulted. This entity may have bizarre histologic findings and should be distinguished from other aggressive lesions like placental site trophoblastic tumor, epithelioid trophoblastic tumor and squamous cell carcinoma.